RESPONS PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) TERHADAP PEMBERIAN PUPUK KALIUM DAN PUPUK MAGNESIUM - Muhammad Haikal Avesena; Putra Utama; Julio Eiffelt Rossafelt Rumbiak; Abdul Hasyim Sodiq (BPFP Universitas Bengkulu, 2026)
Shallots are an economically important horticultural crop widely consumed by Indonesian consumers, and the increasing demand for shallots indicates that this commodity has strong potential for sustainable development. The production potential of shallots can be enhanced through the application of potassium and magnesium fertilizers. This study aimed to increase shallot production through the application of potassium and magnesium fertilizers at appropriate dosage levels. This study was a factorial experiment arranged in a Randomized Block Design (RBD). The first factor was the dosage of potassium fertilizer, consisting of four levels: 0, 75, 150, and 225 kg/ha. The second factor was the dosage of magnesium fertilizer, consisting of four levels: 0, 125, 250, and 375 kg/ha. Each treatment combination was replicated three times, resulting in a total of 48 experimental units. The results of the study showed that potassium fertilizer treatment of 150 kg/ha had a significant effect on plant height (44.1 cm), plant weight (73.7 g), bulb diameter (2.52 cm), fresh bulb weight (38.3 g), and dry bulb weight (27.5 g). Meanwhile, magnesium fertilizer treatment of 250 kg/ha had a significant effect on plant height (46.2 cm), plant weight (83 g), bulb diameter (2.61 cm), bulb length (3.76 cm), fresh bulb weight (44.3 g), and dry bulb weight (31.6 g). The interaction between potassium fertilizer at 75 kg/ha and magnesium fertilizer at 375 kg/ha showed a significant effect on the number of leaves (23.7 leaves), number of tillers per clump (5.7 tillers), and number of bulbs (7 bulbs). These findings suggest that the combined application of potassium at 150 kg/ha and magnesium at 250 kg/ha is recommended as an effective fertilization strategy to enhance shallot growth and yield.